ADOPTING SMART DEVICES IN TEACHING FOR THE ACQUISITION OF 21ST CENTURY EMPLOYABILITY SKILLS BY STUDENTS IN STATE UNIVERSITIES IN CAMEROON - Agbor Emmanuel Oben; Endeley Margaret Nalova; Frederick Ashu Ebot (The American Journal of Social Science and Education Innovations, 2023)
This study on adopting smart devices in teaching for the acquisition of 21st century employability skills by students in State Universities in Cameroon had as objective to find out the extent to which the use of smart devices in teaching can enhance the acquisition of 21st-century employability skills by students in state universities in Cameroon. Two research questions guided the study: - To what extent is the use of smart phones in teaching effective in enhancing the acquisition of 21st-century employability skills by students in State Universities in Cameroon? To what extent is the use of Laptops in teaching effective in enhancing the acquisition of 21st-century employability skills by students in State Universities in Cameroon? It was hypothesized that the use of smart devices in teaching does not significantly enhance students’ acquisition of 21st-century employability skills in state universities in Cameroon.The study based on Rogers’ (1962) diffusion of innovation theory, supposing that the adoption of a new idea, behaviour, or product does not happen simultaneously in a social system; rather, it is a process whereby some people are more apt to adopt the innovation than others and Davis (1986) technology acceptance model, which posits that the more a technology is perceived as useful and easy to use, its’ actual usage increases. The study adopted an exploratory sequential research design in a mixed-methods study. The accessible population consisted of 3666 teachers and final-year undergraduate students of eight state universities in Cameroon. Using Krejcie & Morgan (1970), 406 participants from professional faculties in five of the eight long existing state universities in Cameroon, were selected to make up the sample size, comprising 386 final-year undergraduate students, and 20 teachers. The stratified purposive sampling, and purposive sampling techniques were adopted for the study. Online Google forms alongside a paper questionnaire, and an interview guide were adopted as the study instruments. The quantitative data were analysed using SPSS version 25 with the aid of descriptive and inferential statistics. The Spearman rho test was used to test the hypotheses and Analysis of Variance (ANOVA) was used for regression analysis. The qualitative data were analysed thematically. The findings of the study showed that the use of smart phones and laptops in teaching had a significant, moderate, and positive impact on students’ acquisition of 21st-century employability skills (r- value = 0.418**, p-value 0.000< 0.05) in state universities in Cameroon. In conclusion, the findings of the study showed that smart devices do not only help students in information sourcing but enhanced their communication skills, critical thinking & problem solving skills, creativity and team working skills. Based on the findings of the study, it was recommended that the state should make teaching with smart devices a policy in state universities and university teachers should be encouraged to use of smart Phones and Laptops in teaching to enhance students’ acquisition of 21st century employability. It was also recommended that government should take appropriates measure to resolve the energy crisis, internet disruptions and training challenges both teachers and students are currently facing.